Validation of the Italian version of the Neuroception of Psychological Safety Scale (NPSS) - Andrea Poli; Mario Miccoli (Heliyon, 2024)
Research on the neuroscience of fear in both humans and non-humans has suggested that a lack of acquisition of safety cues might be a biological hallmark of posttraumatic stress disorder (PTSD). Danger perception, and in particular, feeling as one's own life is in danger, is thought to represent a major predictor of PTSD. Persistent danger perception is concurrently associated with a persistence of lack of safety. However, despite several research efforts, no validated psychometric tools exist regarding psychological safety as a unique core construct in the domain of a soothing-contentment system. By including social, compassionate, and bodily components, the Neuroception of Psychological Safety Scale (NPSS), neurophysiologically rooted in the polyvagal theory, aims to specifically assess psychological safety. Originally developed in English, we employed a rather large non clinical sample to validate our Italian translation of the NPSS (n = 338) and the scale was found to retain a three-factor structure. In light of its positive moderate correlations with the Unconditional Self-Kindness Scale (ρ = 0.376) and the Self-Compassion Scale-Short-Form (ρ = 0.481), good convergent validity and robust psychometric properties were shown by the NPSS. The Subjective Traumatic Outlook Questionnaire (ρ = −0.283) and the three subscales of the Body Perception Questionnaire-22—Body Awareness (ρ = −0.103), Supradiaphragmatic Reactivity (ρ = −0.234), and Body Awareness/Subdiaphragmatic Reactivity (ρ = −0.146)—were found to have weak negative correlations with the NPSS, which further demonstrated its good discriminant validity. Eventually, the NPSS was found to show good test-retest reliability (intraclass correlation coefficient = 0.922; three-week time interval), and its usage is fostered in clinical and research contexts where the evaluation of psychological safety is of relevance.